1996
DOI: 10.1007/bf02044129
|View full text |Cite
|
Sign up to set email alerts
|

Toxic shock syndrome due to group C Streptococci A case report

Abstract: This case illustrates how an early diagnosis and prompt antibiotic therapy can determine a more favorable outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Compounds from group G streptococci have been partially characterized that are mitogenic and can produce fevers and induce lethal activity in the endotoxin hypersensitivity model of toxic shock syndrome (2). Since numerous cases of STSS caused by group C (15,28,43) and group G (15, 30) streptococci have been reported, it is possible that other novel superantigens are involved. Further study of this important family of toxins will improve our understanding of superantigen biology and evolution and may ultimately lead to improved treatments for severe streptococcal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Compounds from group G streptococci have been partially characterized that are mitogenic and can produce fevers and induce lethal activity in the endotoxin hypersensitivity model of toxic shock syndrome (2). Since numerous cases of STSS caused by group C (15,28,43) and group G (15, 30) streptococci have been reported, it is possible that other novel superantigens are involved. Further study of this important family of toxins will improve our understanding of superantigen biology and evolution and may ultimately lead to improved treatments for severe streptococcal disease.…”
Section: Discussionmentioning
confidence: 99%
“…equisimilis strains having group A antigen rather than group C or G antigen have also been reported (Bert & Lambert-Zechovsky, 1997;Brandt et al, 1999;Katsukawa et al, 2002). Many recent studies have reported that this organism causes invasive and systemic streptococcal infections like GAS (Natoli et al, 1996;Wagner et al, 1996; Hirose et al, 1997; Kugi et al, 1998;Barnham et al, 2002;Cohen-Poradosu et al, 2004;Hashikawa et al, 2004). The organism has also been reported to cause a wide variety of human infections such as pharyngitis, cellulitis, sepsis, meningitis and endocarditis (Woo et al, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…Recently, case reports referring to STSS caused by the Lancefield group C streptococci (GCS and G i and GGS, respectively) have also accumulated (1,2,11,14,17,24,27,30,35,38,45,49; H. Watanabe (ed. ), Rep. 24th Hyg.…”
mentioning
confidence: 99%